A study on the level of ergonomic awareness among staff in UiTM Jengka, Pahang / Maisarah Aminah Kamarudin and Nooraishah Abd Halim - Kamarudin, Maisarah Aminah; Abd Halim, Nooraishah (2013)
Much attention has been focused on the relationship between office ergonomic application and job performance, this study aim to identify the level of ergonomic awareness among 150 academic and 150 administrative staff in UiTM Jengka, Pahang. Data were gathered through questionnaires and was being analyzed by using Statistical Package for Social Science (SPSS) version 20. The major finding shows that high level of ergonomic awareness among academic staff compare to administration staff. Furthermore, the independent variables are found to be among the strongest variable with the ergonomic awareness. Conclusion and recommendation were also discussed.